Effects of Transcutaneous Neuromuscular Electrical Stimulation on Swallowing Disorders: A Systematic Review and Meta-Analysis. (August 2020) - Sun, Yuanyuan; Chen, Xiaoyun; Qiao, Jianhong; Song, Guixiang; Xu, Yuedong; Zhang, Yan; Xu, Dongmei; Gao, Wei; Li, Yunfeng; Xu, Cuiping
Abstract : Objective: The aim of the study was to evaluate the efficacy of transcutaneous neuromuscular electrical stimulation on swallowing disorders. Design: MEDLINE/PubMed, Embase, CENTRAL, Web of science, and PEDro were searched from their earliest record to August 1, 2019. All randomized controlled trials and quasi-randomized controlled trial were identified, which compared the efficacy of neuromuscular electrical stimulation plus traditional therapy with traditional therapy in swallowing function. The Grading of Recommendations Assessment, Development and Evaluation approach was applied to evaluate the quality of evidence. Results: Eight randomized controlled trials and three quasi-randomized controlled trials were included. These studies demonstrated a significant, moderate pooled effect size (standard mean difference = 0.62; 95% confidence interval = 0.06 to 1.17). Studies stimulating suprahyoid muscle groups revealed a negative standard mean difference of 0.17 (95% confidence interval = −0.42, 0.08), whereas large effect size was observed in studies stimulating the infrahyoid muscle groups (standard mean difference = 0.89; 95% confidence interval = 0.47 to 1.30) and stimulating the suprahyoid and infrahyoid muscle groups (standard mean difference = 1.4; 95% confidence interval = 1.07 to 1.74). Stimulation lasting 45 mins or less showed a large, significant pooled effect size (standard mean difference = 0.89; 95% confidence interval = 0.58 to 1.20). The quality of evidences was rated as low to very low. Conclusions: There is no firm evidence to conclude on the efficacy of neuromuscular electrical stimulation on swallowing disorders. Larger-scale and well-designed randomized controlled trials are needed to reach robust conclusions. Abstract : Supplemental digital content is available in the text.